Avaliação do processo de cicatrização de lesões, tratadas com laser de baixa intensidade, através de sistema de aquisição e tratamento de imagem - Renato Mendes Almeida (2006)
Wound healing is a complex dynamic process characterized as a sequence of responses from several types of cells (epithelial, inflammatory, blood platelet, and fibroblasts) that interact to restore tissue complexion. It starts right after occurring an injury with an inflammatory stage, which is followed by granulation and, finally, by epithelization. Several therapies are proposed to help and accelerate the healing process such as the use of natural plant bandaging, use of antiseptics, ultrasonic waves, galvanic currents, hyperbaric chambers, laser beam, etc. The evolution process of wound healing is usually measured through the lesion reduction evolution with the use of pachymeters. This study was carried out in order to evaluate the efficiency of low-intensity laser on wound healing in mice through the analysis of lesion reduction with the aid of a pachymeter and of a system of acquisition and images treatment. Thirty Wistar mice were used for this trial; they were divided into 3 groups (A, B, and C), each one with 10 mice. All of them underwent two lesions on both sides of their backs (right and left). Group A got a visible low-intensity laser treatment, bilaterally, i.e. on both lesions. Group B got a visible lowintensity laser treatment, unilaterally, i.e. only one on the left side. Group C (control group) did not get any kind of treatment, having a natural evolution of the healing process. The standardized lesions were accomplished by using a cylindrical inoxidable steal staff with 10 cm long and 12 mm diameter, that was cooled into liquid nitrogen for 10 minutes, and then used to bruise the back of the mouse for a minute. The analysis of lesion reduction with a pachymeter was done by the transversal and horizontal linear measures of the lesion and subsequent calculus of its area. For attaining the technique of acquisition and images treatment photos were taken with a digital camera at a standard distance from the camera to the back of the animals. In the sequence, the treatment of images was carried out by software that evaluated the process of lesion reduction by calculating the area according to the number of pixels. After comparative analysis of the results, it was evidenced that the group treated with the use of laser beam bilaterally had a better acceleration in the healing process when compared with the control group. In Group B, the left lesions that were treated with laser had a healing process similar to the right lesions not treated with it, what seems to indicate a systemic effect of the laser light, since those right lesions not treated of Group B had healed faster than the lesions of the control group. It was also noticed that the system of evaluation of wound healing process through the technique of acquisition and images treatment in the visible mode grants a better metrological reliability for the process control.